Microneedle-array patches loaded with hypoxia-sensitive vesicles provide fast glucose-responsive insulin delivery - Yu, Jicheng; Yuqi Zhang; Yanqi Ye; Rocco DiSanto; Wujin Sun; Davis Ranson; Frances S. Ligler; John B. Buse; Zhen Gu (Proceedings of the National Academy of Sciences - PNAS, 2015)
A glucose-responsive âclosed-loopâ insulin delivery system mimicking the function of pancreatic cells has tremendous potential to improve quality of life and health in diabetics. Here, we report a novel glucose-responsive insulin delivery device using a painless microneedle-array patch (âsmart insulin patchâ) containing glucose-responsive vesicles (GRVs; with an average diameter of 118 nm), which are loaded with insulin and glucose oxidase (GO â) enzyme. The GRVs are self-assembled from hypoxia-sensitive hyaluronic acid (HS-HA) conjugated with 2-nitroimidazole (NI), a hydrophobic component that can be converted to hydrophilic 2-aminoimidazoles through bioreduction under hypoxic conditions. The local hypoxic microenvironment caused by the enzymatic oxidation of glucose in the hyperglycemic state promotes the reduction of HS-HA, which rapidly triggers the dissociation of vesicles and subsequent release of insulin. The smart insulin patch effectively regulated the blood glucose in a mouse model of chemically induced type 1 diabetes. The described work is the first demonstration, to our knowledge, of a synthetic glucose-responsive device using a hypoxia trigger for regulation of insulin release. The faster responsiveness of this approach holds promise in avoiding hyperglycemia and hypoglycemia if translated for human therapy.